Towards a New Generation of Hormone Therapies: Design, Synthesis and Biological Evaluation of Novel 1,2,3-Triazoles as Estrogen-Positive Breast Cancer Therapeutics and Non-Steroidal Aromatase Inhibitors - Huda R. M. Rashdan; Mohamad T. Abdelrahman; Anna Chiara De Luca; Maria Mangini (MDPI AG, 2024)
Aromatase inhibitors (AIs) show promising features as drugs to treat estrogen-responsive breast cancer as they block aromatase activity, the key enzyme in estrogen synthesis. The current AIs approved by the Food and Drug Administration for breast cancer treatment present severe adverse effects. For these reasons, it is important to develop of new AIs that are more specific and sensitive. In this paper, we report the synthesis and the characterization of new nonsteroidal aromatase AIs containing triazoles moieties for the treatment of hormone-dependent breast cancer in post-menopausal women. A new series of 1,2,3-triazole based molecules were successfully synthetized and their chemical structures were determined from the spectral data (FT-IR, 13C NMR, 1H NMR, mass spectroscopy) and micro-analytical data. Additionally, the physical properties of the newly synthesized derivatives were reported. The novel compounds were also tested for their anticancer activity in both breast cancer (MCF7 and T-47D) and normal breast (MCF 10A) cell lines, evaluating their effect on cell proliferation, migration, and invasion. The results revealed that the compounds exhibited promising and specific anti-cancer action.